PREFERENSI PEMILIHAN CALON PASANGAN HIDUP DITINJAU DARI KETERLIBATAN AYAH PADA ANAK PEREMPUAN - ANNA ARMEINI RANGKUTI; DEVI OKTAVIANI FAJRIN (Journal of Research and Measurement in Psychology, 2015)
This study aims to determine the effect of father involvement on mate selection preferences in his young adult daughters. Researcher used scale quantitative methods psychology. Researcher used adapted instrument, namely Nurturant Fathering Scales and Father Involvement Scale subscale Reported Father Involvement Scale for variable of father involvement and used instrument created by researcher for variable mate selection preferences. There are 96 samples which is a father who has daughters ages 18-25 and is unmarried with accidental sampling. The data processing used in the testing of hypotheses analytics logistic regression. The result of this research is there is no influence of father involvement on mate selection preferences in his young adult daughters. But when viewed from the value of Odds Ratio of 2,571 indicates that the father has opportunity to choose the family background preferences of the prospecive life partner of his daughters of 2,571 times compared of the personal characteristics preference of the prospecive life partner of his daughters. That is the father has opportunity to choose the family background preference of their prospecive life partner of his daughters compared of their personal characteristics preference even though the value is only 2,571.